Thermoregulatory and physiological responses of nonpregnant, mid-gestation, and late-gestation sows exposed to incrementally increasing dry bulb temperature. (4th June 2021) - McConn, Betty R; Gaskill, Brianna N; Schinckel, Allan P; Green-Miller, Angela R; Lay, Donald C; Johnson, Jay S
Abstract: Gestating sows may be more susceptible to increasing dry bulb temperatures (T DB ) due to greater metabolic heat production and increased body mass, especially as gestation advances. However, there are few studies on the thermoregulatory and physiological responses of sows at differing gestation stages exposed to gradually increasing temperatures. The study objective was to determine the thermoregulatory and physiological responses of nonpregnant ( n = 12; parity 3.27 ± 0.86), mid-gestation (59.7 ± 9.6 d pregnant, n = 12; parity 3.25 ± 0.83), and late-gestation (99.0 ± 4.8 d pregnant, n = 12; parity 3.33 ± 0.75) sows exposed to increasing TDB . Prior to the experiment (5.0 ± 0.7 d), jugular catheters were placed in all sows. During the experiment, the TDB was increased incrementally by 2.45 ± 0.43 °C every 60 min from 19.84 ± 2.15 to 35.54 ± 0.43 °C over 400 min, and relative humidity was recorded at 40.49 ± 18.57%. Respiration rate (RR ), heart rate (HR ), skin temperature, and vaginal temperature were measured, and blood samples were obtained via the jugular catheter every 20 min. Data were analyzed using PROC MIXED in SAS 9.4. RR increased at a lower TDB ( P < 0.01) in late-gestation sows compared with mid-gestation and nonpregnant sows, but no differences were detected between mid-gestation and nonpregnant sows. Overall, late-gestation sows had greater RR ( P < 0.01; 23 ± 2 breaths per min [brpm ]) compared with mid-gestation (16 ± 2 brpm) and nonpregnant (15 ± 2 brpm) sows. Late-gestation sows had an overall greater HR ( P < 0.01; 84 ± 5 beats per min [bpm ]) than mid-gestation (76 ± 5 bpm) and nonpregnant (69 ± 5 bpm) sows. Late-gestation sows had overall reduced bicarbonate and total carbon dioxide levels ( P = 0.02; 23.89 ± 1.97 and 25.41 ± 2.07 mmol/L, respectively) compared with mid-gestation (27.03 ± 1.97 and 28.58 ± 2.07 mmol/L, respectively) and nonpregnant (26.08 ± 1.97 and 27.58 ± 2.07 mmol/L, respectively) sows. Moreover, late-gestation sows had overall greater nitric oxide levels ( P < 0.01; 248.82 ± 34.54 µM) compared with mid-gestation (110.47 ± 34.54 µM) and nonpregnant (41.55 ± 34.54 µM) sows. In summary, late-gestation sows appear to be more sensitive to increasing TDB as indicated by thermoregulatory and physiological responses when compared with mid-gestation or nonpregnant sows. The results from this study provide valuable information regarding thermoregulatory thresholds of sows at differing gestation stages.